Predicting Success - Lahey, David (Ascent Audio, 2020)
Make the right hires every time, with an analytical approach to talent Predicting Success is a practical guide to finding the perfect member for your team. By applying the principles and tools of human analytics to the workplace, you'll avoid bad culture fits, mismatched skillsets, entitled workers, and other hiring missteps that drain the team of productivity and morale. This book provides guidance toward implementing tools like the Predictive Index®, behavior analytics, hiring assessments, and other practical resources to build your best team and achieve the best outcomes. Written by a human analytics specialist who applies these principles daily, this book is the manager's guide to aligning people with business strategy to find the exact person your team is missing. An avalanche of research describes an evolving business landscape that will soon be populated by workers in jobs that don't fit. This is bad news for both the workers and the companies, as bad hires affect outcomes on the individual and organizational level, and can potentially hinder progress long after the situation has been rectified. Predicting Success is a guide to avoiding that by integrating analytical tools into the hiring process from the start.
Online resource; Title from title page (viewed July 14, 2020)
Keywords: Business; Affaires; Audiobooks